2015
DOI: 10.1021/jp508471v
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Inhibits Amyloid Formation

Abstract: Amyloid fibrils are large aggregates of misfolded proteins, which are often associated with various neurodegenerative diseases such as Alzheimer’s, Parkinson’s, Huntington’s, and vascular dementia. The amount of hydrogen sulfide (H2S) is known to be significantly reduced in the brain tissue of people diagnosed with Alzheimer’s disease relative to that of healthy individuals. These findings prompted us to investigate the effects of H2S on the formation of amyloids in vitro using a model fibrillogenic protein he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 60 publications
1
36
0
Order By: Relevance
“…As sulfhydration offers a protective barrier on protein cysteine residues from irreversible oxidative modifications (Filipovic et al, 2018), it first protects the proteome from unwanted oxidative stress and prevents the need to synthesize new proteins to replace those that have been damaged. It also offers neuroprotection by preventing protein misfolding and amyloid formation linked to a number of neurodegenerative diseases (Rosario-Alomar et al, 2015). Most importantly, it enhances the anti-aging and cytoprotective activities of longevity and metabolism associated proteins such as, but not limited to, glyceraldehyde phosphate dehydrogenase (GAPDH) (Gao et al, 2015;Mustafa et al, 2009), nuclear factor κB (NF-κB) (Sen et al, 2012), endothelial ATP-sensitive potassium channels (Mustafa et al, 2011), sirtuin 1 (SIRT1) (Du et al, 2019), and the E3 ubiquitin ligase parkin (Vandiver et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…As sulfhydration offers a protective barrier on protein cysteine residues from irreversible oxidative modifications (Filipovic et al, 2018), it first protects the proteome from unwanted oxidative stress and prevents the need to synthesize new proteins to replace those that have been damaged. It also offers neuroprotection by preventing protein misfolding and amyloid formation linked to a number of neurodegenerative diseases (Rosario-Alomar et al, 2015). Most importantly, it enhances the anti-aging and cytoprotective activities of longevity and metabolism associated proteins such as, but not limited to, glyceraldehyde phosphate dehydrogenase (GAPDH) (Gao et al, 2015;Mustafa et al, 2009), nuclear factor κB (NF-κB) (Sen et al, 2012), endothelial ATP-sensitive potassium channels (Mustafa et al, 2011), sirtuin 1 (SIRT1) (Du et al, 2019), and the E3 ubiquitin ligase parkin (Vandiver et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Rosario-Alomar et al investigated the nature of H 2 S interactions with disulfide bonds using NR spectroscopy. 70 It was found that the sulfur atom of H 2 S becomes endogenously incorporated in protein disulfide bonds, which lead to the formation of trisulfides (SSS).…”
Section: Non-aromatic Amino Acids: Disulfide Bondsmentioning
confidence: 99%
“…DUVRR spectra (C) of native HEWL (red), HEWL fibrils (blue) and spherical aggregates formed in the presence of H 2 S (black); spectra were normalized using the aromatic amino acid Raman band around 1600 cm −1 for comparison 70. …”
mentioning
confidence: 99%
“…In order to rule out intensity biases due to local fluctuations in the enhancement factor as well as in surface density and local molecular orientation of the samples, which could influence the signal measured from the type A and type B samples, we normalized the intensity of the main peaks in the 1000–1030 and 1500–1680 cm −1 regions with respect to the corresponding intensity of the Phe mode at 1003 cm −1 ( I / I 1003 , Figure ) on a spectrum‐by‐spectrum basis. This latter mode (as well as the 1027 cm −1 mode), in fact, is poorly affected by the environment and frequently used as “internal” reference for the analysis of biological samples . We note that the amide I as well as the amide II modes exhibit almost overlapping I / I 1003 interval values in both type A and type B oligomers and their average values approach the Phe mode at 1003 cm −1 .…”
Section: Resultsmentioning
confidence: 74%
“…This latter mode (as well as the 1027 cm −1 mode), in fact, is poorly affected by the environment and frequently used as "internal" reference for the analysis of biological samples. [49,50] We note that the amide I as well as the amide II modes exhibit almost overlapping I/I 1003 interval values in both type A and type B oligomers and their average values approach the Phe mode at 1003 cm −1 . Conversely, the other modes appear largely more intense in type A than in type B spectra.…”
Section: Resultsmentioning
confidence: 78%